ANALISIS HAMBATAN BELAJAR PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA MATERI FAKTOR DAN KELIPATAN DI KELAS IV FASE B SEKOLAH DASAR - Pakpahan, Gritia Putri; Eka Sastrawati; Issaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the learning barriers of students in class IV phase b of elementary school on mathematics and multiples learning material. The research method used in this research is the qualitative method. The subjects of this research were class IV students at SD Negeri 121/I Muara Singoan. Data collection techniques are carried out through observation, interviews and tests. The results of this research indicate that there are learning obstacles for class IV students at SD Negeri 121/I Muara Singoan which refer to students' knowledge so that errors occur in working on question. Starting from students not being able to describe the material to solving factors and multiples questions related to everyday life. Apart from that, there are students who make mistakes in the steps in completing them.